26-4s+s=9s

Simple and best practice solution for 26-4s+s=9s equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26-4s+s=9s equation:


Simplifying
26 + -4s + s = 9s

Combine like terms: -4s + s = -3s
26 + -3s = 9s

Solving
26 + -3s = 9s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-9s' to each side of the equation.
26 + -3s + -9s = 9s + -9s

Combine like terms: -3s + -9s = -12s
26 + -12s = 9s + -9s

Combine like terms: 9s + -9s = 0
26 + -12s = 0

Add '-26' to each side of the equation.
26 + -26 + -12s = 0 + -26

Combine like terms: 26 + -26 = 0
0 + -12s = 0 + -26
-12s = 0 + -26

Combine like terms: 0 + -26 = -26
-12s = -26

Divide each side by '-12'.
s = 2.166666667

Simplifying
s = 2.166666667

See similar equations:

| 5/2x=5/2+5/2+x+x | | -22=-3(8+x)+2(4x+1) | | 6y+1=16ysquared | | 2(3)-5-3(2(3)-7)= | | -4=-5x+4x | | -30=3v | | -5p+2=48 | | b-ax=3c | | -.001385x^2-.076x+50.135=0 | | 2x+12+13=13 | | x^3+9x^2-15x-25=y | | P(x)=(x+4)[x-(2+5i)][x-(2-5i)] | | 510=x(5)+135 | | -6n-15=6n+15 | | 18x=18+18+x+x | | 6=-34-5d | | 9s=26-4s | | -1.385E-3x^2-.076x+50.135=0 | | 7-3x-12=16 | | 6(8k+2)=-36 | | 6(8k+2)=36 | | 2(-3-5)= | | 2X-6=5X-4 | | 10p+2=2(-3p-9)+3(-10-3p) | | 0=-1.385E-3x^2-.076x+50.135 | | 634768945670+7342569834756=53653456+n | | 3x^2+18x+75=0 | | 2+5a-2=-5 | | 63x^2-24=-66x | | -y-16=y-16 | | 3x=3+3+x+x | | 0.08x-0.40(40+x)=0.20(40) |

Equations solver categories